Investigating waqf property resources of institutional mutawalli in Malaysia - Abd Mutalib, Hasyeilla; Maamor, Selamah; Hashim, Suraiya; Abd. Wahab, Norazlina; Zainol, Zairy; Shakrani, Mohd Saharudin (2017)
Purpose - The purpose of this study is to investigate the waqf property resources of institutional mutawalli in Malaysia.Methodology - This study employs qualitative methods by investigating four selected institutional mutawalli in Malaysia in term of their property resources.The selected institutional mutawalli selected by using purposive sampling method.This study has performed formal and semistructured interview with waqf manager, deputy CEO, waqf coordinator and manager of waqf development unit as a representative to the institutional mutawalli.Findings - In this study, the waqf property resources of institutional mutawalli can be categorized into three elements such as i) waqf property information; ii) waqf property resources; and iii) frequency of the resources acceptance.Those elements can give some general insight related to the each institutional mutawalli waqf property resources.